Severe Repeated Hypotension Occurred after Rocuronium Administrations in a Morbidly Obese Patient: A Case Report - Fabio Silvio Mario Araimo Morselli; Paolo Tordiglione; Ilaria Scarpa; Francesco Zuccarini; Giovanni Rosa (Global Journal of Anesthesiology - Peertechz Publications, 2014)
Rocuronium has the most rapid onset of action among the nondepolarizing neuromuscular blocking drugs; doses of 0.6-0.9 mg/ Kg guarantee a complete block in about 60-90 seconds and good or excellent intubating conditions in 60 seconds [1,2]. Its pharmacokinetics and pharmacodynamics can be influenced by different factors as age, inhaled anesthetics, hepatic and renal insufficiency, hypothermia, gender and obesity [3-8]. Rocuronium has been shown to cause less histamine release and cardiovascular instability than benzylisoquinolinum neuromuscular blocking agents such as atracurium and mivacurium [9], however it can act as an antigen: in our clinical experience three acute reactions occurred after its administration in the same patient.